‘MARKING THEIR OWN HOMEWORK’: TRUST AND AUDIENCE MEASUREMENT IN THE AUSTRALIAN DIGITAL ADVERTISING INDUSTRY - Kininmonth, Samuel Stanley (AoIR Selected Papers of Internet Research, 2019)
This paper examines how the Australian advertising industry debates trust in the infrastructures of digital advertising. The advertising industry is undergoing a major change as digital advertising is increasingly dominated by new advertising technology (adtech) players and major tech companies such as Facebook and Google. These new companies which rely on automated systems of ad targeting, pricing and placement to control large amounts of digital advertising inventory and offer new more ‘efficient’ ways to micro-target advertising. Yet these companies have garnered reputations for misrepresenting their numbers; a problem compounded by Google and Facebook’s reticence to provide independent audience verification. This has led to a high degree of mistrust from Australian advertisers. Neither Google or Facebook offers serious third-party auditing, leading many in the advertising industry to say that they are ‘marking their own homework’. In this paper I ask, how is trust of measurement and verification infrastructures debated within the digital advertising industry? Is it fair to compare businesses that distribute advertising in very different ways? I answer these questions through qualitative analysis of submissions made to the Australian Competition and Consumer Commission (ACCC) as part of its current Digital Platforms Inquiry (DPI) in 2018 and 2019. I also draw on summaries of four public forums the ACCC held in 2018 as well as wide reading in the advertising industry trade press. This paper aims to contribute to a better understanding of the role standards and measures play within industry and how they relate to trust during industry transformation.